Experiencing ritual : a new interpretation of African healing - Turner, Edith L. B., 1921- (Series in contemporary ethnography., 1992)
"The scene is Zambia in 1985. A patient has been invaded by the tooth of a dead hunter, a spirit object which causes her much pain. Only a drum ritual can cure it. The company starts to sing and drum, and when at last the dramatic climax breaks, the anthropologist sees a six-inch blob--a kind of plasma or gray spherical ghost--emerging from the patient's back." "Experiencing Ritual is Edith Turner's account of how she sighted a spirit form while participating in the Ihamba ritual of the Ndembu. Turner's experience with the Ndembu is extensive; from 1951 to 1954 she and her husband, the preeminent anthropologist Victor Turner, conducted fieldwork among them. This fieldwork formed the basis for Victor Turner's highly influential work, The Drums of Affliction. In that study, Victor Turner analyzed the Ihamba in terms of its social and psychological functions, but dismissed the Ndembu view that the real context of the Ihamba is spiritual." "When Edith Turner returned to the Ndembu in 1985, she learned what she and Victor did not learn during their early fieldwork--how to understand the Ihamba in Ndembu terms. Through her richly detailed analysis of the ritual and her willingness to make the spirit central to her analysis, she presents a view not common in anthropological writings--the view of millions of Africans--that ritual is the harnessing of spiritual power." "This provocative and challenging work will be of interest to students and scholars of anthropology, African studies, and religious studies."--Jacket